True Fish Farming Story in Lake Victoria Basin (TRUE-FISH Project) - Tibihika, Papius (WorldFish, 2022)
WorldFish Genetics Workshop 2022 - ppt presentation about a True Fish farming story in Lake Victoria Basin.